Halth Workers' Knowledge about The Use of Electronic Medical Records: A Literature Review - Saadah, Alfina Aisatus; Wahyuni, Titin; Firdaus , Abidatu Zahrotul; Yulianita, Novi Eka (Babali Nursing Research, 2024)
Introduction: The knowledge of health workers will affect their skills in carrying out the quality of medical records. The development of knowledge is so fast that health workers will quickly fall behind if they do not take advantage of various things to update the latest developments. The purpose of this study was to identify the knowledge of health workers about the use of electronic medical records (EMR).Methods: This study used a literature review design with a qualitative approach to the data obtained in the form of literature review study data collection. Researchers collected 15 articles or scientific journals that have been published to analyze the knowledge of health workers in using EMR.Results: The percentage of health workers who knew about the use of EMR was more than 50% in 10 articles and less than 50% in 5 articles.Conclusion: The percentage of health workers who know about the use of EMR is relatively high. The level of knowledge is still low due to the lack of training and computer skills for officers and the lack of understanding by officers regarding the benefits of EMR for health facilities.